Lemierre Syndrome: Clinical Update and Protocol for a Systematic Review and Individual Patient Data Meta-analysis - Sacco, Clara; Zane, Federica; Granziera, Serena; Holm, Karin; Creemers-Schild, Dina; Hotz, Michel-André; Turpini, Elena; Valentini, Adele; Righini, Christian; Karkos, Petros D.; Verhamme, Peter; Di Nisio, Marcello; Konstantinides, Stavros; Pecci, Alessandro; Barco, Stefano; on behalf of the (Hämostaseologie, 2019)
Lemierre syndrome usually affects otherwise healthy adolescents or young adults and occurs at an overall rate of 1 to 10 cases per million person-years with an estimated fatality rate of 4 to 9%. Diagnostic criteria remain debated and include acute neck/head bacterial infection (often tonsillitis caused by anaerobes at high potential for sepsis and vascular invasion, notably Fusobacterium necrophorum) complicated by local vein thrombosis, usually involving the internal jugular vein, and systemic septic embolism. Medical treatment is based on antibiotic therapy with anaerobic coverage, anticoagulant drugs and supportive care in case of sepsis. Surgical procedures can be required, including drainage of the abscesses, tissue debridement and jugular vein ligation. Evidence for clinical management is extremely poor in the absence of any adequately sized study with clinical outcomes. In this article, we illustrate two cases of Lemierre syndrome not caused by Fusobacterium necrophorum and provide a clinically oriented discussion on the main issues on epidemiology, pathophysiology and management strategies of this disorder. Finally, we summarize the study protocol of a proposed systematic review and individual patient data meta-analysis of the literature. Our ongoing work aims to investigate the risk of new thromboembolic events, major bleeding or death in patients diagnosed with Lemierre syndrome, and to better elucidate the role of anticoagulant therapy in this setting. This effort represents the starting point for an evidence-based treatment of Lemierre syndrome built on multinational interdisciplinary collaborative studies.
Keywords: Lemierre syndrome; venous thromboembolism; bacterial infection; anticoagulant treatment; Fusobacterium necrophorum